Analisis Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Konsumen Pada Usaha Peternakan Ruminansia (Studi Kasus CV. Amanah Saebur di Kecamatan Tambun Selatan, Kabupaten Bekasi) - Arzethy, Patricia Karin; Abadi, Slamet; Yusiana, Ekalia (Universitas Galuh, 2024)
CV. Amanah Saebur is a enterpriseoccupied in livestock borough, founded in 2007, and became an officially licensed entity in 2019. The company needs to maintain a marketing mix strategy to gain a competitive advantage. This research purposely to analyse teh impact of the trading alloy be composed of price, yield, furtherance, location, person, cultivate, also act substantiation simultaneously and partially on consumer purchasing decisions. The method use establisedthe attempt in this study uses the accidental instance method, namely determining the sample by chance meeting with the researcher, also unqualified attempt of 100 person in this research. Exemplar material use were primary also secondary data. Data aggregation methods used are questionary, debriefing, surveillance, and then literature study. The data aggregation technology was do by deliver questionary. Instrument testing uses validity and reliability and then being transformed use using the Method of Succesive Interval (MSI). The analysis technique and hypothesis testing use multiple option deterioration analyzes withbeforehead enumerate classic presumption regularity exam, multicollinearity exam, heteroscedasticity exam. The output this research are (1) price, product, promotion, location, person, process, and physical evidence act substantiation partially influence obtainresolve. (2) price, product, promotion, person, process, and physical evidence partially impact obtain resolv, location dont has act leverage on purchasing decisions.